ENHANCING TEACHERS’ EMOTIONAL WELL-BEING THROUGH PARENTAL INVOLVEMENT; STRATEGIES AND IMPLICATIONS FOR EDUCATIONAL POLICY - Zohaib Hasan Sain (Nurul Jadid University, 2024)
This study aims to identify effective forms of parental involvement in fostering teachers' emotional well-being and to explore its implications for educational policy. The research employs a qualitative approach with a case study method conducted at elementary schools at Lahore. Data collection techniques include in-depth interviews, participatory observations, and document analysis. The findings indicate that emotional support in parental involvement, contributions of parental involvement to enhancing teachers' job satisfaction, and parental participation in school activities as a support for teachers' emotional well-being play crucial roles in supporting teachers' emotional welfare. Recognition and appreciation of parental involvement were also found to be significant motivational factors. This research contributes by reinforcing the understanding of the importance of synergy between schools, parents, and the community in creating a positive and supportive learning environment. However, the study is limited to a single location and does not account for broader variations in gender and age. Therefore, further research is needed to obtain a more comprehensive perspective and to support more targeted educational policy-making.